Evaluation of miR-200c-3p and miR-421-5p levels during immune responses in the admitted and recovered COVID-19 subjects - Abdolahi, Shahrokh; Hosseini, Maryam; Rezaei, Ramazan; Mohebbi, Seyed Reza; Rostami-Nejad, Mohammad; Mojarad, Ehsan Nazemalhosseini; Mirjalali, Hamed; Yadegar, Abbas; Asadzadeh Aghdaei, Hamid; Zali, Mohamad Reza; Baghaei, Kaveh (Infection, genetics and evolution, 2022)
Angiotensin-converting enzyme 2 (ACE2) acts as a key receptor for the spike of SARS-CoV-2. Two main microRNAs (miRs), miR-200c-3p and miR-421-5p, are considered to modulate the expression of ACE2 gene and alterations in the expression of these miRNAs may influence the outcomes of COVID-19 infection. Accordingly, we examined whether miRNAs directing ACE2 expression altered in the SARS-CoV-2 infection. 30 patients with COVID-19 included in the study. At the time of admission and discharge, the expression of miR-200c-3p and miR-421-5p, inflammatory cytokine IL-6, and regulatory T cells' expression profiles (CD4, CD25, and Foxp3) were examined using quantitative real-time PCR method. At the time of admission, the expression levels of miR-200c-3p and miR-421-5p as well as CD4, CD25, and Foxp3 significantly decreased while IL-6 expression notably enhanced. However, by the time of discharge, the expression levels of the genes were opposite to the time of admission. Moreover, Pearson correlation analysis indicated that IL-6 expression negatively correlated with Foxp3 and miR-200c-3p expressions despite miR-421-5p and miR-200c-3p positively correlated at admission time. By manipulating miR-200c-3p and miR-421-5p expressions and controlling the ACE2 level, it is plausible to modulate the inflammation by reducing IL-6 and maintenance tolerance hemostasis during COVID-19 infection. •miRNAs could serve as a novel prognostic marker for SARS-CoV-2 infection.•hsa-miR-200c-3p directly targets ACE2 mRNA leading to decreased ACE2 expression.•miR-421-5p cause a balance between inflammatory and anti-inflammatory processes.•Assessing the levels of miRNA 200c and 451-5p could be important for coronavirus COVID-19 (SARS-CoV-2) patients.